Explor Dig Dis 2022
DOI: 10.37349/edd.2022.00002
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in metabolic dysfunction associated fatty liver disease: mechanisms, diagnostic and therapeutic implications

Abstract: The prevalence of metabolic dysfunction-associated fatty liver disease (MAFLD) is increasing rapidly worldwide due to the obesity epidemic. Advanced stages of the MAFLD, such as non-alcoholic steatohepatitis (NASH) with advanced fibrosis or cirrhosis are affecting global health. Extracellular vesicles (EVs) are released by all cell types and are important in cell-to-cell communication and maintaining homeostasis, but they also play a role in the pathogenesis of various diseases. EVs contain biological informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…10 Recently, we reviewed the literature on the role of EVs in cell to cell communication in the context of MASLD. 11 Several studies investigated the content of EVs and demonstrated the presence of bioactive proteins as well as various RNA species (mRNA, miRNA), also in the context of MASLD. 12 miRNAs have the capacity to modulate various aspects of cellular function.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Recently, we reviewed the literature on the role of EVs in cell to cell communication in the context of MASLD. 11 Several studies investigated the content of EVs and demonstrated the presence of bioactive proteins as well as various RNA species (mRNA, miRNA), also in the context of MASLD. 12 miRNAs have the capacity to modulate various aspects of cellular function.…”
Section: Introductionmentioning
confidence: 99%
“…Their remarkable stability positions them as promising biomarkers with potential applications in disease diagnosis and prognosis. 11,13 Senescence is a state of (almost) irreversible cell cycle arrest. Induction of senescence in stellate cells has been proposed as a potential intervention to prevent and/ or reverse activation of HSCs and we have observed a reciprocal relation between the expression of activation markers and senescence markers in HSCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs have the capacity to modulate various aspects of cellular function. Their remarkable stability positions them as promising biomarkers with potential applications in disease diagnosis and prognosis 11,13 . Senescence is a state of (almost) irreversible cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%